Chronic Prostatitis/Chronic Pelvic Pain Syndrome and Incomplete Response to Antibiotics: Fungal Infectious like Candida A. to be taken into Consideration in Some Subpopulations - Mauro, Luisetto; Ahmad, Khan Farhan; Rasool, Mashori Ghulam; Luca, Cabianca; Yurevich, Latyshev Oleg (Archives of Case Reports, 2026)
The aim of this work is to submit a specific case report of chronic prostatitis with incomplete response to antibiotics and the role played by Candida A, in the literature, it is reported that it is necessary to consider this pathogen in a specific subpopulation. The early consideration of this eventuality make possible to avoid dangerous delay in the right etiologic treatment. In this work, It is used a clinical pharmacy and pharmaceutical care approach. In this research is then submitted a specific case report to better explain the rationale.